Solow and heterogeneous labor: A neoclassical explanation of wage inequality - Jürgen Meckl; Stefan Zink (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2001)
The paper integrates human-capital investments of heterogeneous individuals into a neoclassical growth framework. The accumulation of physical capital changes relative factor prices and thus incentives to acquire skills, thereby altering the composition of the labor force. This interplay between the accumulation of human and physical capital provides a theoretical foundation for several important observations on wage inequality (e.g., the non-monotonic evolution of the skill premium) without having to hinge on specific exogenous shocks. Additional incorporation of wage rigidities emphasizes the trade off between residual wage inequality and employment opportunities for unskilled labor that is consistent with country-specific evidence.
Keywords: I21; J31; O15; 330; Wage inequality; human-capital investment; transitional adjustment dynamics